Nusyuz Wife as a Result of Transferring Child Custody Rights from Wife to Husband from the Perspective of the Compilation of Islamic Law - Said, Raja Anggun Kusuma; Harahap, Mhd. Yadi; Fatimah, Fatimah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Marriage is a physical and mental bond between a man and a woman with the aim of forming an eternal and happy family according to God Almighty. In a marriage bond, husband and wife have the responsibility to fulfill each other's needs to build a harmonious and peaceful family. Divorce is the breakup of a family because one or both partners decide to leave each other so that they stop performing their obligations as husband and wife. The existence of divorce between husband and wife raises new problems, especially for children, which include the problem of caring for children's rights (Hadhanah). The concept of Maslahah mursalah, the main purpose of this concept is to realize benefit and eliminate harm, this principle aims to keep the child physically and mentally protected from his divorced parents. The first decision is, with Number 361/Pdt.G/2018/PA.Dps, in this case the Plaintiff in his lawsuit dated November 27, 2020 has filed a child custody lawsuit registered at the registrar of the Denpasar Religious Court with Number: 400/Pdt.G/2020/PA.Dps. Analysis in terms of benefit, in the Denpasar Religious Court Decision, the Judge not only decides and transfers child custody based on the law, but also in the interests of the child, which is better and greater if the four children are cared for by their mother rather than their father, as for the form of transferring custody of children who are not yet mumayyiz to the biological mother (nusyuz) shows that the legal basis of the Panel of Judges in handling this case is based on Maslahah and justice for the benefit of the child.